Phylogenomic analysis of the Candida auris-Candida haemuli clade and related taxa in the Metschnikowiaceae, and proposal of thirteen new genera, fifty-five new combinations and nine new species - Liu, F.; Hu, Z.-D.; Zhao, X.-M.; Zhao, W.-N.; Feng, Z.-X.; Yurkov, A.; Alwasel, S.; Boekhout, T.; Bensch, K.; Hui, F.-L.; Bai, F.-Y.; Wang, Q.-M. (Persoonia, 2024)
Candida is a polyphyletic genus of asexually reproducing yeasts in the Saccharomycotina with more than 400 species that occur in almost all families of the subclass and its name is strongly connected with the infectious disease candidiasis. During the last two decades, approximately half of the Candida species have been reassigned into more than 36 already existing genera and 14 newly proposed genera, but the polyphyletic feature of the genus largely remained. Candida auris is an important, globally emerging opportunistic pathogen that has caused life-threatening outbreaks in healthcare facilities worldwide. This species belongs to the Candida auris - Candida haemuli (CAH) clade in the Metschnikowiaceae , a clade that contains multidrug-resistant clinically relevant species, but also species isolated from natural environments. The clade is phylogenetically positioned remotely from the type species of the genus Candida that is Candida vulgaris (currently interpreted as a synonym of Candida tropicalis ) and belongs to the family Debaryomycetaceae . Although previous phylogenetic and phylogenomic studies confirmed the position of C. auris in the Metschnikowiaceae , these analyses failed to resolve the position of the CAH clade within the family and its delimitation from the genera Clavispora and Metschnikowia . To resolve the position of the CAH clade, phylogenomic and comparative genomics analyses were carried out to address the phylogenetic position of C. auris and related species in the Metschnikowiaceae using several metrics, such as the average amino acid identity (AAI) values, the percentage of conserved proteins (POCP) and the presence-absence patterns of orthologs (PAPO). Based on those approaches, 13 new genera are proposed for various Candida and Hyphopichia species, including members of the CAH clade in the Metschnikowiaceae . As a result, C. auris and related species are reassigned to the genus Candidozyma . Fifty-five new combinations and nine new species are introduced and this will reduce the polyphyly of the genus Candida .